Formulation, Characterization and Evaluation of Innovative O/W Emulsions Containing Curcumin Derivatives with Enhanced Antioxidant Properties - Evdokia Dalla; Ioanna Koumentakou; Nikolaos Bikiaris; Evangelia Balla; Smaro Lykidou; Nikolaos Nikolaidis (MDPI AG, 2022)
In the present study, a series of semisolid Oil in Water (O/W) emulsions containing different Curcumin (Cur) derivatives (Cur powder, Cur extract and Cur complexed with β-cyclodextrin) in varying concentrations, were prepared. Initially, Dynamic Light Scattering (DLS), microscopy, pH and viscosity measurements were performed to evaluate their stability over time. Moreover, the effect of the active cosmetic substances on the Sun Protection Factor (SPF), antimicrobial and antioxidant properties of the prepared emulsions was investigated. It was observed that emulsions containing Cur extract and Cur β-cyclodextrin complex presented great viscosity and pH stability for up to 90 days of storage contrary to the emulsions containing Cur powder which showed unstable behavior due to the formation of agglomerates. All samples presented SPF values between 2.6 and 3.2. The emulsions with Cur in all forms exhibited high antioxidant activity, whereas the emulsion containing Cur β-cyclodextrin complex presented the highest value. Despite their improved stability and antioxidant activity, the emulsions containing Cur extract and Cur-β-cyclodextrin exhibited a low percentage of antimicrobial activity against E. coli and Staphylococcus bacteria. Instead, the emulsions containing Cur powder presented a reduction rate over 90 % against E. coli and Staphylococcus colonies.